HUBUNGAN PROFIL LIPID DENGAN PROGRESIVITAS DIABETES MELITUS TIPE 2 - Angiesta Pinakesty; Restu Noor Azizah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introduction: Diabetes mellitus (DM) is a non-communicable disease that has increased from year to year. Type 2 diabetes mellitus is not caused by lack of insulin secretion, but is caused by the failure of the body's cells to respond to the hormone insulin (insulin resistance). Insulin resistance was found to be a major contributor to atherogenic dyslipidemia. Dyslipidemia in DM risks 2 to 4 times higher than non-DM. Although dyslipidemia has a great risk for people with type 2 diabetes mellitus, this conventional risk factor only explains a portion (25%) of excess cardiovascular risk in type 2 DM. Discussion: In uncontrolled type 2 DM patients, LDL oxidation occurs faster which results from an increase in chronic blood glucose levels. Glycemic control as a determinant of DM progressivity is determined through HbA1c examination. HbA1c levels are associated with blood triglyceride levels. Meanwhile, triglyceride levels are associated with total cholesterol and HDL cholesterol levels. HbA1c levels are also associated with LDL cholesterol levels. Conclusion: There is a relationship between lipid profile and the progression of type 2 diabetes mellitus. Keywords: type 2 diabetes mellitus, dyslipidemia, HbA1c, glycemic control, lipid profile